MODEL OF IMPLEMENTING ISLAMIC EDUCATION VALUES IN STRENGTHENING TOLERANT BEHAVIOR IN PLURAL SOCIETIES - Achmad Anwar Abidin (Universitas Islam Malang, 2021)
Abstract Ngepeh hamlet is one of the hamlets in Rejoagung village, Ngoro sub-district, Jombang district. In this village there are three adherents of different religions, namely Islam, Christianity and Hindusm. Even though they have different religions, they still life in harmony and tolerance. It is proven by the existence of various places of worship from people of different religions, namely two churches, one temple, one Jami' Mosque and several mushola (prayer rooms). Instilling values in society needs to be investigated as a model in managing pluralism in rural communities. This research is a qualitative research with the type of case study. Data collection techniques using participant observation techniques, in-depth interviews, and documentation. To determine the informants used purposive sampling and snowball sampling techniques. The findings of this study are a value inculcation model which is divided into two forms, namely inter-community and intra-community models. The inter-community model is carried out in the nobility association with activities in the form of discussions, savings and loans activities, art performances and mass rituals. In order to strengthen tolerance in the community, this community prioritizes cultural da'wah tactics, namely by accommodating local wisdom. In the intra-community model through religious education in Islamic religious activities. ta'alum or a learning process with indoctrination techniques.Keywords: model of implementing islamic education values, tolerant behavior